Sosialisasi Penerapan Konsep Ekowisata Dalam Pengembangan Desa Wisata di Desa Dasan Griya, Kecamatan Lingsar Lombok Barat - Virgota, Arben; Farista, Baiq; Widiyanti, Astrini; Rahayu, Rachmawati Noviana; Julisaniah, Nur Indah; Muspiah, Aida (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
Dasan Geria Village possesses unique biophysical and sociocultural potential that can be developed into an ecotourism area. Its biophysical attractions include natural landscapes such as several waterfalls, namely Ponjok Waterfall, Bangket Bawo Waterfall, Teburun Nanas Waterfall, and Temburun Bukal Waterfall. The local community’s activities, such as the production of palm sugar (gula semut) and traditional kris-making, also offer distinctive attractions for tourists. However, this initiative is still constrained by challenges related to the development and management of village-based ecotourism, as well as efforts to optimize its potential, benefits, and active community participation. This community service initiative aims to disseminate the concept of ecotourism for implementation in Dasan Geria Village. The application of the ecotourism concept can be initiated through awareness-raising activities, focus group discussions (FGDs), and workshops involving local residents, village authorities, and academics. The people of Dasan Geria hold a positive perception and express agreement with the adoption of the ecotourism concept, while also hoping to receive financial support for its implementation. In applying this concept, consistent and sustainable guidance and assistance for the community in managing and developing ecotourism are essential